The lemonade crime - Davies, Jacqueline, 1962- (Boston [Mass.] : Houghton Mifflin Books for Children, 2011)
When money disappears from fourth-grader Evan's pocket and everyone thinks that his annoying classmate Scott stole it, Evan's younger sister stages a trial involving the entire class, trying to prove what happened.
"Sequel to The lemonade war"--Dust jacket.
4.6
3-6
3-6
Keywords: Brothers and sisters -- Juvenile fiction; Forgiveness -- Juvenile fiction; Human behavior -- Juvenile fiction; Schools -- Juvenile fiction; Trials -- Juvenile fiction; Behavior -- Fiction; Brothers and sisters -- Fiction; Forgiveness -- Fiction; Schools -- Fiction; Trials -- Fiction; Forgiveness -- Fiction; Human behavior -- Fiction; School stories; Siblings -- Fiction; Trials -- Fiction